2009
DOI: 10.1063/1.3190522
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence properties of Eu2+-activated CaSi2O2N2: Redshift and concentration quenching

Abstract: Highly efficient CaSi 2 O 2 N 2 :Eu 2+ green phosphors were synthesized via solid-state reaction method. The produced phosphors are effectively excited with UV-vis light of wavelength between 300 and 460 nm and emit a single, intense, and broad emission band centered at 538 nm. The experimental results and their analysis suggest that the energy transfer mechanism should occur due to dipole-dipole interactions among Eu 2+ ions, resulting in a shift in emission spectrum toward longer wavelengths with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The authors further suggested that the red-shift arose from the formation of Mn 2+ pairs, which have a lower energy level compared to that at lower concentrations of Mn 2+ [149]. While high concentration of activators in the host are known to quench luminescence severely [279][280][281], Zhang's study showed that the ML of CaZnOS over a wide concentration of Mn 2+ activators (0.1 to 10 mol%) is intense enough to be observed by the naked eye in a dark room (see Movie in Ref. [149]).…”
Section: Concentration Effect Of Luminescent Centersmentioning
confidence: 99%
“…The authors further suggested that the red-shift arose from the formation of Mn 2+ pairs, which have a lower energy level compared to that at lower concentrations of Mn 2+ [149]. While high concentration of activators in the host are known to quench luminescence severely [279][280][281], Zhang's study showed that the ML of CaZnOS over a wide concentration of Mn 2+ activators (0.1 to 10 mol%) is intense enough to be observed by the naked eye in a dark room (see Movie in Ref. [149]).…”
Section: Concentration Effect Of Luminescent Centersmentioning
confidence: 99%
“…In order to emit light in the visible region of electromagnetic spectrum, synthesized phosphors have to absorb in near UV to blue spectral range thereby limiting the activators to Eu 2+ and Ce 3+ that can be used in phosphors. Among these silicon oxynitrides, Eu doped MSi 2 O 2 N 2 (M = Sr, Ba, Ca) is found to be excellent candidates owing to better thermal and chemical stability with a broad absorption band spanning from UV to blue region of the electromagnetic spectrum 13–21. SrSi 2 O 2 N 2 is isotypic with EuSi 2 O 2 N 2 and crystallizes in triclinic structure and has P1(1) space group symmetry 13.…”
Section: Introductionmentioning
confidence: 99%
“…When the Eu 2+ concentration increased, the distance among the Eu 2+ ions became shorter, consequently leading to the increase in energy transfer within the Eu 2+ ions. Therefore, the increasing nonradiative energy transfer resulted in the red shift in emission wavelength 31 …”
Section: Resultsmentioning
confidence: 99%